'Digital First': homelessness and data use in an online service environment. Issue 2 (3rd April 2019) - Humphry, Justine
ABSTRACT: A contribution to the growth in data use is the need to access a wide range of services on the internet. In this paper, I examine the implications for people experiencing homelessness of data use necessitated by large-scale digitisation of government services and other everyday interactions. The findings from a published study are reviewed and used in conjunction with reports, websites, and inclusion policy literature to support a discussion of the impacts of whole-of-government digital transformation agendas in Australia and internationally. I argue online services drive demand for smartphones and push up data consumption, creating new burdens of cost and connectivity for people who are homeless, who rely heavily on the mobile for online access. I argue for a systematic approach to address access and affordability barriers in a data-driven society, including updating universal service measures, expanding low-income subsidies to include home broadband and mobile data and voice, and connecting inclusion efforts with other equity and justice approaches.